Utility of trichoscopy - Rachita S Dhurat (Wolters Kluwer Medknow Publications, 2018)
Trichoscopy is evolving as an indispensable aid to the dermatologist by providing valuable clues on dermatoscopy of the scalp and hair. Trichoscopy presents as a bridging tool between clinical and histological diagnosis. It is useful to distinguish congenital atrichia from other forms of childhood hair loss such as alopecia universalis. There are a set of women who present with chronic hair loss without any discernible reduction in hair density over the crown. Such early forms are often overlooked, and clinical evaluation may not be adequate to make the right diagnosis. Trichoscopy has been widely used as a diagnostic as well as a prognostic tool to measure anisotrichosis in cases of overt androgenetic alopecia and female pattern hair loss (FPHL) and to distinguish them from telogen effluvium. It can be used to distinguish FPHL from diffuse and subtotal alopecia areata (AA) as well as trichotillomania from AA which can have similar clinical presentations. Trichoscopy also helps in monitoring treatment response in patients of AA. It is also useful in diagnosing infectious conditions such as noninflammatory tinea capitis, seborrheic dermatitis, piedra, and pediculosis. Trichoscopy represents a valuable, noninvasive and low-cost technique, still underutilized, to rapidly differentiate clinically frequent hair disorders.